Web transcript verification using dual check digit as secure number - Abd Halim, Muhamad Rais (2016)
An academic transcript is an official document that stated the record of the achievement of a student in every subject they took during the studies in their learning institution. It also covers other details such as the grade point average and cumulative grade point average for each semester. This document needs to present during job interview along with other relevant certificates. Some organizations will go through details into academic transcripts to justify the suitability of the candidate to work with them. There are chances that this document will be forged to suit the needs of the organization. Therefore, to solve this problem, this research proposes a method using check digit to verify academic transcript authenticity. The result shows that our method that combines ISBN Modulus 10 and UPC Modulus 10 techniques outperform others and can detect almost all the forgery attempts. The outcome of this research is very important to ensure that no forgery can be done in the academic transcript and by this only genuine professionals can works in a given fields.